Clinician Use of Standardized Assessments Following a Common Elements Psychotherapy Training and Consultation Program - Lyon, Aaron R. (2015)
Despite increasing emphasis on the implementation of evidence-based treatments in community service settings, little attention has been paid to supporting the use of evidence-based assessment (EBA) methods and processes, a parallel component of evidence-based practice. Standardized assessment (SA) tools represent a key aspect of EBA and are central to data-driven clinical decision making. The current study evaluated the impact of a statewide training and consultation program in a common elements approach to psychotherapy. Practitioner attitudes toward, skill applying, and use of SA tools across four time points (pre-training, post-training, post-consultation, and follow-up) were assessed. Results indicated early increases in positive SA attitudes, with more gradual increases in self-reported SA skill and use. Implications for supporting the sustained use of SA tools are discussed, including the use of measurement feedback systems, reminders, and SA-supportive supervision practices.